Reportaż „skonwergowany”. Dzienniki kołymskie J. Hugo-Badera jako hybryda medialna - Frukacz, Katarzyna (Postscriptum Polonistyczne, 2020)
The article analyses the relation between the process of media convergence and hybridization of contemporary reportage. The integration of old and new media in a single journalistic report of hybrid character is being analysed here. The author presents this phenomenon using Dzienniki kołymskie by J. Hugo-Bader as an example. It is a work which oscillates between travel diary and travel reportage, it was first published in sections on an Internet press portal. Additionally, the specific character of multimedia journalism and the poetics of digital reportages are commented on in the article.